2003
DOI: 10.2116/analsci.19.877
|View full text |Cite
|
Sign up to set email alerts
|

Wire-Coated Silver(I) Ion-Selective Electrode Based on 2-Mercaptobenzothiazole (MBT) Ionophore: Application to the Determination of Silver in Real Samples

Abstract: A new wire-coated silver ion-selective electrode with a wider concentration range (10 -7 M -10 -1 M) was developed using 2-mercaptobenzothiazole (MBT) as a neutral ionophore. An optimum mixture of PVC, ionophore, dioctylphtalate (DOP) as a plasticizer and sodium tetraphenylborate (NaTPB) as an ion-pairing agent was used in preparing the coatings. The effect of various parameters, such as the electrode bed nature, coating composition and solution pH, on the efficiency of the electrode is described. It has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…The results indicated that the detection limits and dynamic ranges of these CWEs are influenced by the nature of the conductive bed, and the detection limit decreases with decreasing the resistivity of the beds ( Table 2). This is true as the electrode potential performance is attributed to the electron exchange mechanism at the coating-bed interface and to the ion-exchange process at the coating-solution interface [26,27]. Silver has the lowest resistivity between the studied elements (1.62 cm −1 ), and as shown in Table 2, the CWEs based on this element have the lowest detection limits.…”
Section: Preliminary Studiesmentioning
confidence: 97%
“…The results indicated that the detection limits and dynamic ranges of these CWEs are influenced by the nature of the conductive bed, and the detection limit decreases with decreasing the resistivity of the beds ( Table 2). This is true as the electrode potential performance is attributed to the electron exchange mechanism at the coating-bed interface and to the ion-exchange process at the coating-solution interface [26,27]. Silver has the lowest resistivity between the studied elements (1.62 cm −1 ), and as shown in Table 2, the CWEs based on this element have the lowest detection limits.…”
Section: Preliminary Studiesmentioning
confidence: 97%
“…MBT has been used as the chelating agent for the preconcentration and spectrometric determination of Ag(I) [15][16][17], Cu(II) [18], Hg(II) [19,20], Au(III), Pt(IV), and Pd(II) [21]. It has also been used in the construction of ion-selective and modified electrodes [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al proposed amido-thiourea immobilized glass beads packing for separation and preconcentration of silver(I) in FIA, which was coupled with AAS. 8 There were also potentiometric detections by silver(I) selective electrodes using 2-mercaptobenzothiazole 9 as an ionophore and using calyx [4]arene as a carrier. 10 However, non of these FIA methods were applicable to practical analyses of silver(I) in coexistence with excess amounts of other metal ions such as copper(II).…”
Section: Introductionmentioning
confidence: 99%